ANALISIS KONSEP MERDEKA BELAJAR DALAM PERSPEKTIF PENDIDIKAN KEWARGANEGARAAN - Lubis, Nur Kholila; Suyanti, Suyanti; Dharma, Surya; Yunita, Sri (Universitas Negeri Medan, 2023)
Abstract: The aim of this research is to analyze the concept of independent learning from a citizenship education perspective. This research was conducted using a qualitative approach using the literature study method. The data analysis process in this research includes data reduction, data display, verification, and drawing conclusions. The results of this research analyze the concept of independent learning from two perspectives, namely the citizenship education perspective in the curricular dimension and the citizenship education perspective in the socio-cultural dimension. In these two dimensions, it shows the compatibility between the concepts formed in independent learning and the goals of citizenship education. The role of teachers in transformation is the main determinant in the success of the independent curriculum itself. It can be concluded that the concept of an independent curriculum from a citizenship education perspective has correlations and the same goals, where teachers are the center of its success.Keyword: Independent Curriculum, Independent Learning, Citizenship Education. Abstrak: Tujuan dilakukannya penelitian ini adalah untuk menganalisis konsep merdeka belajar dari perspektif Pendidikan kewarganegaraan. Penelitian ini dilakukan melalui pendekatan kualitatif dengan metode studi literatur. Proses analisis data dalam penelitian ini meliputi reduksi data, display data, verifikasi, serta penarikan kesimpulan. Hasil dari penelitian ini, menganalisis konsep merdeka belajar dari dua perspektif, yakni perspektif Pendidikan kewarganegaraan dalam dimensi kurikuler dan perspektif Pendidikan kewarganegraaan dimensi sosio kultural. Dalam kedua dimensi tersebut, menunjukkan kesesuaian antara konsep yang dibentuk dalam merdeka belajar dengan tujuan Pendidikan kewarganegaraan. Peran guru dalam transformasi menjadi penentu utama dalam keberhasilan kurikulum merdeka itu sendiri.Dapat disimpulkan, konsep kurikulum merdeka dari perspektif Pendidikan kewarganegaraan memiliki korelasi dan kesamaan tujuan, dimana guru menjadi pusat keberhasilannya.Kata Kunci: Kurikulum Merdeka, Merdeka Belajar, Pendidikan Kewarganegaraan.